Developing and Initially Validating the Youth Mental Health Literacy Scale for Ages 11–14 - Riebschleger, Joanne; Grové, Christine; Kelly, Kimberly; Cavanaugh, Daniel (Frontiers in Psychiatry, 2022)
Despite rising rates of youth mental health disorders and suicides, most youth lack access to accurate, non-stigmatized mental health information. Instead, many describe people with mental illness as violent and incompetent. Mental health literacy aligns with resilience theory. It assumes that youth that have accurate mental health information will have less stigmatized views of mental illness and will be more likely to seek help earlier should mental health symptoms arise. Accurate, non-stigmatized mental health information is especially needed for Children of a Parent or other Family Member that has a mental illness (COPFMI) since they are more likely to acquire a mental illness than children who do not have a family member with a mental illness. COPFMI youth are in need of the same mental health information as general population youth but they can also benefit from knowing how to deal with a family member's mental health disorder. Based on many foundation studies and key stakeholder input from parents, educators, mental health providers, child welfare providers, and especially youth, an emerging Youth Mental Health Literacy (YMHL) scale was developed and validated for measuring the mental health literacy levels of youth ages 11–14. The scale provides a full scale score of youth mental health literacy. It has subscales of knowledge of mental illness and recovery; stigma, help seeking for self/others; coping with stress; and dealing with family mental health challenges. The validation study indicated support for a unidimensional structure for each of the refined subscales. The subscales showed suitable reliability as evaluated by several measures of internal consistency. While the scale needs further study with larger samples of youth, it is hoped that the scale can yield mental health literacy outcome data that can help mental health literacy programs to build evidence-based programs that may, in turn, help prevent, delay, or ameliorate mental health disorders among youth.